Health risk behaviours of stroke patients in the Western Cape, South Africa - D. Biggs; A. Rhoda (AOSIS, 2008)
Stroke is a leading cause of death and a major cause of disability globally. Individuals with physical disabilities, including thosewho have suffered a stroke are at risk of secondary complications due to the impact of their disability, which may be exacerbated by their lifestylechoices. The aim of the present study was to determine the health riskbehaviours and factors that influence these behaviours of stroke patients inthe Metropole Region of the Western Cape, South Africa. A cross - sectionalsurvey, utilizing a self-administered questionnaire on a convenient sampleof 417 stroke patients, was used to collect data. A sub-sample of 10 parti-cipants was purposively selected for in-depth, face-to-face interviews.Approximately forty percent (40.3%) of the participants did not engage in physical exercise. While 30.2% smoked only9% abused alcohol. A significant association was found between age and smoking (p<0.002). Information gathered in the in-depth interviews revealed factors that influenced the behaviours of the participants. These factors includedlack of financial resources and lack of access to information. As participants were found to be at risk of secondarycomplications because of poor lifestyle choices, there is a clear need to implement health promotion programmes topromote well-ness enhancing behaviours in order to enhance the quality of health of patients who have suffered astroke in the Western Cape, South Africa.